Synaptotagmin‐11 regulates the functions of caveolae and responds to mechanical stimuli in astrocytes. Issue 2 (20th December 2019) - Yan, Shuxin; Wang, Yalong; Zhang, Yujia; Wang, Le; Zhao, Xiaofang; Du, Cuilian; Gao, Pei; Yan, Feng; Liu, Fengwei; Gong, Xiaoli; Guan, Yuan; Cui, Xiuyu; et al.
Abstract: Caveolae play crucial roles in intracellular membrane trafficking and mechanosensation. In this study, we report that synaptotagmin‐11 (Syt11), a synaptotagmin isoform associated with Parkinson's disease and schizophrenia, regulates both caveolae‐mediated endocytosis and the caveolar response to mechanical stimuli in astrocytes. Syt11‐knockout (KO) accelerated caveolae‐mediated endocytosis. Interestingly, the caveolar structures on the cell surface were markedly fewer in the absence of Syt11. Caveolar disassembly in response to hypoosmotic stimuli and astrocyte swelling were both impaired in Syt11‐KO astrocytes. Live imaging revealed that Syt11 left caveolar structures before cavin1 during hypoosmotic stress and returned earlier than cavin1 after isoosmotic recovery. Chronic hypoosmotic stress led to proteasome‐mediated Syt11 degradation. In addition, Syt11‐KO increased the turnover of cavin1 and EH domain‐containing protein 2 (EHD2), accompanied by compromised membrane integrity, suggesting a mechanoprotective role of Syt11. Direct interactions between Syt11 and cavin1 and EHD2, but not caveolin‐1, are found. Altogether, we propose that Syt11 stabilizes caveolar structures on the cell surface of astrocytes and regulates caveolar functions under physiological and pathological conditions through cavin1 and EHD2.